THE ANTIBIOTICS SENSITIVITY TEST ON STAPHYLOCOCCUS AND STREPTOCOCCUS FROM CHRONIC APICAL ABSCESS - Malinda, Yuti; Prisinda, Diani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Prophylactic antibiotics are required as part of root canal therapy for patient with chronic apical abscess. Streptococcus and Staphylococcus are the most common bacteria found in root canals with chronic apical abscess. Resistance to amoxicillin, clindamycin and vancomycin has been increasing year after year, necessitating the use of a sensitivity test. The goal of this research was to determine the sensitivity of Streptococcus and Staphylococcus from root canals with chronic apical abscess to amoxicillin, clindamycin, and vancomycin to make scientific antibiotic selections.Method: Six isolates of Staphylococcus and one Streptococcus from root canals with chronic apical abscess were identified by Remel RapID and tested to 10 g amoxicillin, 2 g clindamycin, and 30 g vancomycin using Kirby-Bauer disk-diffusion sensitivity test. The diameter inhibition zone was measured and interpreted according to the CLSI (Clinical and Laboratory Standards Institute) standard.Result: Three of six Staphylococcus are resistant, one of six are intermediate, and two are sensitive to amoxicillin. While the Streptococcus is sensitive to amoxicillin. In contrast, all Staphylococcus and the Streptococcus are resistant to clindamycin. Whilst four of six Staphylococcus are resistant, two are intermediate, and the Streptococcus is resistant to vancomycin.Conclusion: Staphylococcus sensitivity to amoxicillin and vancomycin are diverse even though resistant to clindamycin. In comparison, the Streptococcus sensitivity to clindamycin and vancomycin is resistant but sensitive to amoxicillin.